The two brothers: quran stories for little hearts - Khan, Saniyasnain (Goodword Books India, 2002)
"The Two Brothers" is a tale that often explores themes of loyalty, jealousy, and the consequences of choices. It typically follows two siblings who have contrasting personalities and values. One brother may be hardworking and generous, while the other is lazy and envious. The story often illustrates how their differing attitudes lead to various outcomes, emphasizing lessons about family ties, the importance of virtue, and the impact of one's actions on relationships. Ultimately, it serves as a reminder of the importance of love and understanding among family members.